Al-Takharuj Sebagai Modernisasi Pembagian Hukum Waris Di Indonesia - Ichsan, Muhammad; Dewi, Erna; Harahap, Nasruddin Khalil; Halomoan Hsb, Putra (Muhammadiyah University of Surabaya, 2024)
Inheritance law is a law that regulates what happens to the property of the deceased, namely the transfer of the estate of the deceased person and the impact on his heirs. Indonesia has three inheritance laws: Customary Inheritance Law, Islamic Heritage Law, and Civil Inheritance Law. Each region has different laws depending on the kinship system it has. Al-Takharruj is a study or discourse that can prove that the modernization of Islamic inheritance law is a reality. The modernization of Islamic inheritance law with al-Takharruj's model could also counter accusations that Islamic inheritance is gender-biased, favoring male inheritance over female inheritance. The practice of al-takharruj in Islamic inheritance law is based on the contract of muawwadah whose conditions satisfy each other. When ownership of a particular property passes from one heir to another, then title to the estate is lost and passes to another heir with whom the estate is settled. This transfer can be done according to the personal will of the heir and does not require the heir to know in advance how many shares he is entitled to. After that, each heir decides to whom the right should be given or should be transferred in the form of a grant.